Cross-Cultural Applicability of Organizational Stressor Indicator for Sport Performers Questionnaire in Ghana Using Structural Equation Modeling Approach - Srem-Sai, Medina; Quansah, Frank; Frimpong, James Boadu; Hagan, John Elvis; Schack, Thomas (Frontiers in Psychology, 2021)
The purpose of this study was to examine the cross-cultural validity of the Organizational Stressor Indicator for Sport Performers (OSI-SP) by investigating its psychometric properties with Ghanaian footballers. The study particularly sought to assess in the Ghanaian context, 1, the convergence validity and reliability of the OSI-SP scale, 2, the discriminant validity of the OSI-SP scale to understand the applicability of the factor structure of the scale, and 3, whether the OSI-SP hypothesized model fits the data collected. The intensity aspect of Arnold et al.’s (2013) 23-item OSI-SP questionnaire was administered to 424 Ghana Premier League (GPL) male footballers who took part in the 202/2021 season. Quality control strategies were put in place to ensure consistency across interpreters and as well improve the validity of the data obtained. The results from a multi-factor first-order confirmatory factor analysis showed some level of convergence validity of the OSI-SP in the Ghanaian context using football players. Out of the 23 items on the original scale, 20 of them met the factor loadings criterion. In assessing the discriminant validity of the OSI-SP scale using Heterotrait-monotrait (HTMT), 50% of the correlation ratios met the criterion for the original 23-item instrument. Comparing the new model (with the 20-items) with the first model (with 23-items) using the Akaike Information Criterion (AIC) value, the model fit indices for the modified model (20-items) appeared better than the original model with 23-items. Generally, there was minimal support was identified for the factor loadings, reliability estimates, and convergent validity as well as discriminant validity of the OSI-SP across the sample of Ghanaian footballers. The implications of these findings are discussed in details.